The Paradoxical Prognostic Value of Endogenous Melatonin in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis of Mild-to-Moderate versus Malignant Infarctions - Merry Angeline; Desak Ketut Indrasari Utami; Kumara Tini (HM Publisher, 2026)
Background: Acute ischaemic stroke (AIS) is a leading global cause of morbidity and mortality. While endogenous melatonin is widely proposed as a neuroprotectant, recent clinical evidence suggests a paradoxical, severity-dependent prognostic relationship. This meta-analysis synthesises evidence regarding this paradox and its prognostic implications. Methods: A systematic search of major databases through March 2026 identified observational studies correlating endogenous melatonin levels with AIS clinical outcomes. Data were stratified by stroke severity phenotype, and standardised mean differences were calculated using random-effects meta-regression models. Results: Ten observational studies comprising 847 AIS patients were included. A striking paradox emerged: in patients with mild-to-moderate stroke, lower melatonin concentrations were associated with poor clinical outcomes. Conversely, in malignant middle cerebral artery infarctions, higher melatonin concentrations were paradoxically linked to worse clinical outcomes, including increased mortality. Extreme overall heterogeneity (I²=97.85%) was substantially resolved (I²=0%) upon proper severity stratification. Conclusion: The prognostic implications of endogenous melatonin fundamentally differ according to stroke severity phenotype. This severity-dependent paradox likely reflects context-dependent alterations in melatonin signalling pathway efficacy. Mechanistic investigations and well-designed prospective trials are urgently warranted to elucidate the underlying pathophysiology.